PANDANGAN DAN OPINI MENGENAI KEBERADAAN HUKUM ADAT DALAM KAITANNYA DENGAN LAND REFORM DI INDONESIA - Achmad Khairi (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
Adat law in Indonesia cannot be denied its existence. This is because adat law has existed from generation to generation since ancestral times before the Indonesian state de jure and de facto existed. But then the problem arises when the state is formed and adat law is "forced" to comply with the national legal regulations that have been formed in Indonesia. One of the quite complicated problems that occur between the adat law community and the national government occurs in the land aspect. Many of the indigenous peoples were then unwilling to hand over the laham which they claimed had been owned by their ancestors for years to the Indonesian government. Even thorny conflicts between the two parties are inevitable, especially in the era of President Soeharto